Implementation of Fluid Monitoring in Toddler at Risk of Hypovolemia Due to Diarrhea - Dianisa Salsabila; Ayu Yuliani Sekriptini; Zaitun (Poltekkes Kemenkes Tasikmalaya, 2026)
Background: Diarrhea remains a major cause of child mortality in developing countries, mainly due to fluid loss leading to hypovolemic shock. Therefore, family-based fluid monitoring is crucial to prevent complications. Objective: This study aimed to implement and describe fluid monitoring in toddlers at risk of hypovolemia due to diarrhea by highlighting the implementation, observing the outcomes, and analyzing the gaps between two subjects. Methods: This study used a descriptive comparative design by recording fluid intake-output, fluid balance, and hypovolemia signs and symptoms using Buku Pemantauan Cairan Si Kecil, a simple parent-friendly fluid monitoring booklet. Results: The results showed that the implementation led to gradual improvement, marked by reduced frequency of diarrhea and vomiting, improved vital signs, and the achievement of positive fluid balance. The subject who received more active parental support showed faster improvement by the third day, while the other subject improved by the fourth day. Factors such as the level of family involvement, recording methods, fever status, and body weight differences also influenced the outcomes. Conclusion: This study shows that intake-output recording by parents using a simple medium could facilitate a real-time hydration status monitoring. These findings strengthen the relevance of Family-Centered Care in pediatric nursing by positioning parents as collaborative partners in care delivery.